2016
DOI: 10.1371/journal.pone.0154394
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytotoxic T-Lymphocyte-Associated Protein 4 (CTLA4) Gene Polymorphisms with Autoimmune Thyroid Disease in Children and Adults: Case-Control Study

Abstract: Autoimmune thyroid disease (AITD), including Graves disease (GD) and Hashimoto disease (HD), is an organ-specific autoimmune disease with a strong genetic component. Although the cytotoxic T-lymphocyte-associated protein 4 (CTLA4) polymorphism has been reported to be associated with AITD in adults, few studies have focused on children. The aim of our study was to investigate whether the CTLA4 polymorphisms, including -318C/T (rs5742909), +49A/G (rs231775), and CT60 (rs3087243), were associated with GD and HD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 74 publications
2
47
0
3
Order By: Relevance
“…Previous studies also found that the G allele and GG genotype were risk factors for several immune-mediated diseases, such as RA [14], IBD [16], T1D [24], AS [20] and GD [22]. Previous studies also found that the G allele and GG genotype were risk factors for several immune-mediated diseases, such as RA [14], IBD [16], T1D [24], AS [20] and GD [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies also found that the G allele and GG genotype were risk factors for several immune-mediated diseases, such as RA [14], IBD [16], T1D [24], AS [20] and GD [22]. Previous studies also found that the G allele and GG genotype were risk factors for several immune-mediated diseases, such as RA [14], IBD [16], T1D [24], AS [20] and GD [22].…”
Section: Discussionmentioning
confidence: 99%
“…CD28, which is a co-stimulatory molecule, together with B7-1 and B7-2 antigens, activates T cells. Protein tyrosine phosphatase non-receptor type 22 (PTPN22) also serves as a negative factor on TCR signaling [12]. Protein tyrosine phosphatase non-receptor type 22 (PTPN22) also serves as a negative factor on TCR signaling [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, inactivated B16-F10 cells (1x10 6 ) were incubated with splenocytes (1x10 4 ) for 12 h at 37˚C. Release of interferon (IFN) was evaluated by ELISA (DY485, Bio-Rad Laboratories, Inc., Hercules, CA, USA) in the supernatants following culture for 72 h. T cells (1x10 6 ) from the splenocytes were purified, as previously described (32) and co-cultured with fresh DMEM B16-F10 cells for 4 h at 37˚C at the effector, at target ratios of 5:1, 20:1 and 40:1, which were ratios used in a previous study (42). Specific CTL activity to the target cells was determined by MTT cytotoxicity assays, as previously described (43).…”
Section: Splenocyte Collection and Cytotoxic T Lymphocyte (Ctl)mentioning
confidence: 99%
“…лых пациентов с ДТЗ и среди аналогичного количе-ства детей с данным заболеванием. Авторы так же, как и в настоящем исследовании, не выявили су-щественных различий между пациентами старшей и младшей возрастных групп [16]. Ген PTPN22 кодирует лимфоцитарную тирозин-фосфатазу, которая является отрицательным регуля-тором Т-клеточной активации.…”
Section: результатыunclassified